Proteomic Analysis of the Effects of Shenzhu Tiaopi Granules on Model Rats with Type 2 Diabetes Mellitus - Zhao JD; Fang ZH (Diabetes, Metabolic Syndrome and Obesity)
Jin-Dong Zhao,1– 3 Zhao-Hui Fang1– 3 1Department of Endocrinology Two, the First Affiliated Hospital of Anhui University of Chinese Medicine, Hefei, Anhui Province, 230031, People’s Republic of China; 2Center for Xin’an Medicine and Modernization of Traditional Chinese Medicine of IHM, the First Affiliated Hospital of Anhui University of Chinese Medicine, Hefei, Anhui Province, 230012, People’s Republic of China; 3Diabetes Institute, Anhui Academy Chinese Medicine, Hefei, 230012, People’s Republic of ChinaCorrespondence: Zhao-Hui Fang, Department of Endocrinology Two, the First Affiliated Hospital of Anhui University of Chinese Medicine, 117 Meishan Road, Hefei, Anhui Province, 230031, People’s Republic of China, Email fangzhaohui1111@163.comBackground: Shenzhu Tiaopi granule (STG) has antidiabetic functions. Data-independent acquisition proteomic technology is an integral part of systems biology. Herein, proteomics was used to analyse the effects of STG on type 2 diabetes mellitus (T2DM) and the mechanism by which STG normalizes glucose metabolism.Methods: Goto-Kakizaki (GK) T2DM model (Mod) rats, aged 15– 16 weeks and with a fasting blood glucose (FBG) level of ≥ 11.1 mmol/L, were treated with metformin or STG for 12 weeks. Wistar rats aged 15– 16 weeks were included in the control (Con) group. Body weight, FBG, total cholesterol (TC), total triglyceride (TG) levels and low-density lipoprotein (LDL-C) levels were measured, and pathological observation, Western blot analysis and data-independent acquisition proteomics of the liver were performed.Results: Significant differences in FBG, TC, TG, LDL-C (p < 0.01) and pathological liver morphology were observed between the Mod group and Con group, whereas both metformin and STG normalized the glucose and lipid metabolism indicators (p < 0.05 or p < 0.01). In total, 5856 proteins were identified via proteomic analysis, 97 of which were significantly differentially expressed in the liver and affected fatty acid metabolism, unsaturated fatty acid biosynthesis, the peroxisome proliferator-activated receptor (PPAR) signalling pathway, pyruvate metabolism, and terpenoid backbone biosynthesis. Screening identified 10 target proteins, including perilipin‐2 (Plin2), pyruvate dehydrogenase kinase 4, farnesyl diphosphate synthase (Fdps) and farnesyl-diphosphate farnesyltransferase 1. Among these proteins, the key proteins were Plin2 and Fdps, which were found to be associated with the PPAR signalling pathway and terpenoid backbone biosynthesis via relationship networks. Plin2 and Fdps are closely related to hyperglycaemia. STG can downregulate Plin2 and upregulate Fdps (p < 0.01).Conclusion: STG ameliorated hyperglycaemia by significantly altering the expression of different proteins, especially Fdps and Plin2, in the livers of GK rats. These findings may reveal the potential of traditional Chinese medicine for treating T2DM.Keywords: type 2 diabetes mellitus, improving hyperglycaemia, proteomics, Fdps, Plin2, Shenzhu Tiaopi granule